Delayed diagnosis of odontogenic infection: a lesson from altered mental status and abnormal breathing. Issue 11 (9th October 2018) - Sawaoka, Ai; Ito, Toshiki; Yoshida, Takayuki; Muromachi, Koichiro; Sakai, Tomoko; Hamada, Kunio; Tani-Ishii, Nobuyuki; Ito, Akihide
Abstract: Altered mental status is a common, yet challenging, clinical presentation encountered by physicians. Here, we report a case of a 68-year-old Japanese female who was transferred to the emergency department due to faint. The laboratory results showed hyponatremia, ketonuria, hyperglycemia and acute kidney injury without fever or inflammatory findings. Although these abnormalities were corrected, her mental status was exacerbated, and apnea/tachypnea appeared. She was eventually diagnosed with acute apical abscess and recovered immediately after dental extractions. This case suggests that odontogenic infection should be considered in the differential diagnosis of altered mental status and that interdisciplinary dental management, including surgical treatment, should be considered for patients with predisposing factors.